UN General Assembly Resolution 76/262 as a strengthening of the collective response to the use of the veto right in the UN Security Council - Валентин Сердюк (Проблеми Законності, 2024)
The article describes the legal nature of United Nations General Assembly Resolution 76/262 (A/76/L.52) entitled "Standing mandate for a General Assembly debate when a veto is cast in the Security Council", adopted on April 26, 2022. We have analyzed this topic due to its relevance and the emergence of a new procedure of the United Nations General Assembly, aimed at increasing of the transparency and accountability of the United Nations Security Council, as a result of the ineffective activity of the Security Council in crisis in which our world finds itself today, in particular due to armed conflicts in Ukraine and the Middle East, which have led to complex humanitarian consequences. Many states and scientists have been expressing their interest in the issue of Security Council reform for a long time. We deeply researched the Resolution which is the first in a long time and a significant legal instrument that changes the existing mechanism of the functioning of the United Nations and has revived the discussions on the need for a complete reform of the Security Council in accordance with Resolution 62/557 of December 15, 2008. The purpose of the article is an overview of the new Resolution 76/262, namely the reasons and expediency of its adoption, cases of application and its effectiveness in modern conditions. The methodological basis of the study are the following general scientific and special methods of cognition of legal phenomena: the method of the philosophical level – the dialectical method; empirical methods – comparative, observation and description methods; general logical methods – analysis, synthesis; specially-legal method. The article analyzes the main provisions of Resolution 76/262, the reasons for its adoption, examines cases of its application, and draws conclusions about the effectiveness of this resolution. We have differentiated the procedures provided for by Resolution 76/262 "Standing mandate for a General Assembly debate when a veto is cast in the Security Council" and Resolution 377 (V) "Uniting for Peace". We have reviewed the international legal conceptual foundations of the need to apply the resolution. The topic of reforming the United Nations against the backdrop of the current world security crisis is very important and relevant for further research by domestic scientists in order to formulate their own proposals, approaches and scientific justifications in the modern Ukrainian science of international public law, as well as for the scientific enlightenment of society in this of knowledge.